Trends and spatial patterns of 20th century temperature, rainfall and PET in the semi-arid Logone River basin, Sub-Saharan Africa. (July 2020) - Murumkar, Asmita; Durand, Michael; Fernández, Alfonso; Moritz, Mark; Mark, Bryan; Phang, Sui Chang; Laborde, Sarah; Scholte, Paul; Shastry, Apoorva; Hamilton, Ian
Abstract: Sub-Saharan floodplains are sensitive to climatic changes in their upstream drainage basin, a major concern is given the dependency of millions of people for their daily subsistence. Understanding hydroclimatic trends and variability is critical for developing integrated coupled human and natural system models to evaluate future scenarios of vulnerability. Here we describe the historical climatic changes in the Logone River basin using grid-based climatic data during a time of concomitant human hydrological modification of the floodplain. Temporal trends were analysed by comparing two periods i.e. 1901/1921–1961 (pre-1960) and 1961–2013 (post-1960). Trends were analysed spatially based on the basin's two Köppen climatic zones: savanna (Aw) covering the southern upstream areas and semi-arid hot (BSh) covering the northern downstream areas. The results show significant increasing trends in maximum and minimum temperatures and potential evapotranspiration (PET), and non-significant decreasing trends in annual rainfall and number of rainy days, across the study area. These climatic changes on temporal and spatial scales play an important role for the coupled natural and human systems in the Logone floodplain. Highlights: Spatio-temporal climatic variations play an important role in flooding pattern. Maximum and minimum temperatures both increased over time in the basin. Decreasing rainfall and increasing PET trends observed in the watershed. Logone basin is getting warmer, impacting flooding pattern of the semi-arid region. Hence, socioeconomic consequences increasingly impacted in the downstream of the basin.